Vaping Expectancies: A Qualitative Study among Young Adult Nonusers, Smokers, Vapers, and Dual Users - Paul T Harrell; Thomas H Brandon; Kelli J England; Tracey E Barnett; Laurel O Brockenberry; Vani N Simmons; Gwendolyn P Quinn (SAGE Publishing, 2019)
Background: "Expectancies," or beliefs about outcomes, robustly correlate with and predict several behaviors including electronic nicotine delivery system ("e-cigarette") use. However, there is limited qualitative research available regarding relevant e-cigarette vaping expectancies. Objectives: The present study used a qualitative approach to derive and refine e-cigarette expectancy themes among young adults. Methods: We conducted 12 focus groups and two individual interviews with young adult nonusers, e-cigarette vapers, cigarette smokers, and dual users to assess beliefs about the effects of e-cigarettes. After a series of open-ended questions, follow-up questions assessed reactions to domains previously examined in expectancy measures for cigarette smoking and e-cigarette vaping. The constant comparative method was used to derive themes from transcripts. Results: Four main themes ( Positive Reinforcement, Social Benefits, Negative Affect Reduction, Negative Consequences ) emerged from the results. Each theme contained three associated subthemes ( Positive Reinforcement : Sensorimotor Experiences, Taste, Stimulation; Social Benefits : Social Facilitation, Influence on Others, Convenience; Negative Affect Reduction : Stress Reduction, Appetite Reduction, Boredom Reduction; and Negative Consequences : Health Risks, Addiction, Secondhand Effects). Conclusions/importance: Previously identified smoking expectancies appear relevant for young adult vaping, with some notable refinements. Positive reinforcement aspects encompassed aerosol clouds, vaping tricks, and unique flavors. Social benefits included influencing others via social media and competitive activity, as well as the convenience of use in a variety of places. Negative affect reduction was controversial among user groups, but vaping was seen as more interesting than smoking and thus more effective at boredom reduction. Young adults were uncertain regarding negative consequences, but appreciated a potential for secondhand effects. Measure refinement via qualitative research and future field testing can enhance our understanding of this relatively new behavior, supporting tobacco control surveillance, marketing/labeling regulations, and counter-advertising development/evaluation.